Respostas
respondido por:
3
Utlilizaremos a seguinte identidade trigonométrica:
![\cos (2x)=2\cos^{2}(x)-1 \cos (2x)=2\cos^{2}(x)-1](https://tex.z-dn.net/?f=%5Ccos+%282x%29%3D2%5Ccos%5E%7B2%7D%28x%29-1)
Sendo assim, para
, temos
![\cos (2x)=2\cdot \left(\dfrac{1}{3} \right)^{2}-1\\ \\ \cos (2x)=2\cdot \dfrac{1}{9}-1\\ \\ \cos (2x)=\dfrac{2}{9}-1\\ \\ \cos (2x)=\dfrac{2-9}{9}\\ \\ \cos (2x)=-\dfrac{7}{9} \cos (2x)=2\cdot \left(\dfrac{1}{3} \right)^{2}-1\\ \\ \cos (2x)=2\cdot \dfrac{1}{9}-1\\ \\ \cos (2x)=\dfrac{2}{9}-1\\ \\ \cos (2x)=\dfrac{2-9}{9}\\ \\ \cos (2x)=-\dfrac{7}{9}](https://tex.z-dn.net/?f=%5Ccos+%282x%29%3D2%5Ccdot+%5Cleft%28%5Cdfrac%7B1%7D%7B3%7D+%5Cright%29%5E%7B2%7D-1%5C%5C+%5C%5C+%5Ccos+%282x%29%3D2%5Ccdot+%5Cdfrac%7B1%7D%7B9%7D-1%5C%5C+%5C%5C+%5Ccos+%282x%29%3D%5Cdfrac%7B2%7D%7B9%7D-1%5C%5C+%5C%5C+%5Ccos+%282x%29%3D%5Cdfrac%7B2-9%7D%7B9%7D%5C%5C+%5C%5C+%5Ccos+%282x%29%3D-%5Cdfrac%7B7%7D%7B9%7D)
Sendo assim, para
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás